Structural and Biophysical Insights into the Role of CD4 and CD8 in T Cell Activation - Li, Yili; Mariuzza, Roy (Frontiers in Immunology, 2013)
T cell receptors (TCRs) recognize peptides presented by MHC molecules (pMHC) on an antigen-presenting cell (APC) to discriminate foreign from self antigens and initiate adaptive immune responses. In addition, T cell activation generally requires binding of this same pMHC to a CD4 or CD8 co-receptor, resulting in assembly of a TCR–pMHC–CD4 or TCR–pMHC–CD8 complex and recruitment of Lck via its association with the co-receptor. Here we review structural and biophysical studies of CD4 and CD8 interactions with MHC molecules and TCR–pMHC complexes. Crystal structures have been determined of CD8alpha/alpha and CD8alpha/beta in complex with MHC class I, of CD4 bound to MHC class II, and of a complete TCR–pMHC–CD4 ternary complex. Additionally, the binding of these co-receptors to pMHC and TCR–pMHC ligands has been investigated both in solution and in situ at the T cell–APC interface. Together, these studies have provided key insights into the role of CD4 and CD8 in T cell activation, and into how these co-receptors focus TCR on MHC to guide TCR docking on pMHC during thymic T cell selection.